Pengaruh Faktor Demografis (Usia, Jenis Kelamin, dan Penghasilan) Terhadap Kepatuhan Wajib Pajak di Kota Bengkulu - Winny Lian Seventeen; iwin Arnova; Yun Fitriano (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to examine the influence of demographic factors, namely age, gender, and income, on taxpayer compliance in Bengkulu City. The analysis method used is regression analysis with a survey approach and purposive sampling technique to select respondent samples. Data were analyzed using SPSS statistical software. The results show that age, gender, and income significantly influence taxpayer compliance. Age has a significant positive effect on taxpayer compliance. Gender also has a significant effect on taxpayer compliance, where female respondents are more compliant in paying taxes compared to male respondents. Income also has a significant effect on taxpayer compliance, where respondents with higher income tend to be more compliant in paying taxes. The results of this study can provide input for relevant parties in improving taxpayer compliance in Bengkulu City.